Infective endocarditis caused by Pseudomonas stutzeri in a patient with Marfan syndrome: Case report and brief literature review. (2017) - Shalabi, Ahmad; Ehrlich, Tristan; Schäfers, Hans-Joachim; Becker, Sören L.
Abstract: Invasive infections due to Pseudomonas stutzeri have rarely been described and mainly occur in immunocompromised individuals. We report a case of infective endocarditis caused by P. stutzeri after previous cardiac surgery in a Lebanese patient with Marfan syndrome. We review the literature and conclude that this pathogen may be of particular medical relevance in the Mediterranean Basin.